The Influence of Human Resource Development Based on Vision-Mission and Quality Assurance on Increasing Teacher Academic Performance at Labs School Kaizen Gunung Putri Bogor - Turmudzi; Slamet Ahmadi (Yayasan Amerta Insan Unggul, 2024)
This research aims to analyze the influence of human resources (HR) development based on vision and mission and quality assurance on improving the academic performance of teachers at Labs School Kaizen Gunung Putri Bogor. The research method used was quantitative, involving 60 teachers as respondents who were selected using saturated sampling techniques. Data was collected through a questionnaire that has been tested for validity and reliability. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The research results show that vision and mission, HR development, and quality assurance have a significant influence on HR competency. In addition, HR competency was proven to be a significant mediator between independent variables and teacher academic performance. These findings indicate that increasing human resource competency through strengthening vision and mission, human resource development, and quality assurance can be an effective strategy for improving teacher academic performance in these schools. The implications of this research provide recommendations for educational institutions to continue to be committed to developing teacher competence in order to achieve the goal of higher quality educatio.